Monitoring the setting process of mortar by a simple mechanical test. (17th February 2020) - Chan, Chih-Chieh; Lin, Shu-Ken; Lin, Yiching
ABSTRACT: The objective of this study was to investigate the feasibility of using a simple mechanical test to determine the setting time of mortar. The simple mechanical test was carried out on a cantilever PVC pipe filled with fresh mortar. The flexural strain response over time was monitored to investigate the setting process of mortar. The estimated setting time could be compared with that determined by the penetration resistance method. The experimental results show that the strain response of the PVC pipe and mortar can be divided into two stages. The first stage is that the cement mortar has not yet become plastic, and the flexural stress is mainly borne by the PVC pipe. The second stage is that the mortar has become plastic and gradually rigidified and has the ability to bear the flexural stress so that the strain of the PVC pipe decreases with time. Both the initial and final setting times of mortar obtained from the flexural test were in good agreement with those determined by the penetration resistance method. The proposed flexural test can be applied directly to measurement of the setting time of concrete without a need to remove the coarse aggregates larger than #4.